Leaving the Faith: How Religious Switching Changes Pathways to Adulthood among Conservative Protestant Youth. (June 2015) - Glass, Jennifer L.; Sutton, April; Fitzgerald, Scott T.
Research revealing associations between Conservative Protestantism and lower socioeconomic status is bedeviled by questions of causal inference. Religious switching offers another way to understand the causal ordering of religious participation and demographic markers of class position. In this article, we look at adolescents who change their religious affiliation across four waves of data from the National Longitudinal Study of Adolescent Health (Add Health) and then observe their transition to adulthood using four crucial markers—completed educational attainment, age at first marriage, age at first birth, and income at the final wave. Results show that switching out of a Conservative Protestant denomination in adolescence can alter some, but not all, of the negative consequences associated with growing up in a Conservative Protestant household. Specifically, family formation is delayed among switchers, but early cessation of education is not.